2016
DOI: 10.21037/hbsn.2015.10.05
|View full text |Cite
|
Sign up to set email alerts
|

Robotic liver surgery: technical aspects and review of the literature

Abstract: This article provides technical details of robotic liver resections and a review of the current literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 45 publications
1
71
0
6
Order By: Relevance
“…The mortality rate reported in the review was zero, and the morbidity rate ranged from 0 to 43% [27,28], and as shown by Spampinato et al [27], it was similar to laparoscopy, also in case of major hepatectomy (16 vs. 36%).…”
Section: Discussionsupporting
confidence: 55%
“…The mortality rate reported in the review was zero, and the morbidity rate ranged from 0 to 43% [27,28], and as shown by Spampinato et al [27], it was similar to laparoscopy, also in case of major hepatectomy (16 vs. 36%).…”
Section: Discussionsupporting
confidence: 55%
“…As reported by the authors of this paper, following the first laparoscopy assisted donor right hepatectomy in 2006, only 22 pure MIS approach for right sided donor hepatectomy were reported during the following 5 years (1). The report of these pioneer surgeries confirmed the feasibility of highly selected cases in the hands of experienced MIS surgeons (4). Today the number of centers performing almost routinely right and full left MIS liver donor hepatectomy is steadily growing especially in Asian countries.…”
mentioning
confidence: 66%
“…Nevertheless, both techniques were found to be equally efficient in terms of oncologic outcomes, the length of stay, and complication rates [44]. In the same fashion, another review of the literature the same year concluded that robotic hepatic surgery is as effective as laparoscopic and open surgery [45]. A review of the literature specifically dealing with the topic of hepatocellular carcinoma reported a similar statement [46].…”
Section: Hepatobiliary and Pancreatic Surgery: Nothing Is Impossiblementioning
confidence: 94%